1999
DOI: 10.1562/0031-8655(1999)070<0624:hstooc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Targeting of Ovarian Cancer with the Photosensitizer PEG-m-THPC in a Rat Model

Abstract: Photodynamic therapy (PDT) uses light to activate a photosensitizer that has been absorbed or retained preferentially by cancer cells after systemic administration. The first pegylated photosensitizer, tetrakis-(m-methoxypolyethylene glycol) derivative of 7,8-dihydro-5,10,15,20-tetrakis(3-hydroxyphenyl)-21,23-[H]-porphyrin (PEG-m-THPC), was evaluated to target selectively unresectable pelvic ovarian cancer bulks. Our goals were two-fold: (1) to establish an ovarian cancer model suitable for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Photodynamic therapy (PDT) utilizes this effect to treat several types of early stage tumors and other diseases [4][5][6][7]. Typically, PDT involves a two step protocol; firstly, a lightabsorbing compound (the photosensitizer) is taken up (mostly) specifically by target cells [8][9][10][11][12], secondly, the sensitizer is activated by irradiation with visible light of the appropriate energy [13][14][15]. Since the light penetration depth in tissue increases with the wavelength, an absorption maximum at the highest possible wavelength (red / near infrared) is taken for activation of the sensitizer [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) utilizes this effect to treat several types of early stage tumors and other diseases [4][5][6][7]. Typically, PDT involves a two step protocol; firstly, a lightabsorbing compound (the photosensitizer) is taken up (mostly) specifically by target cells [8][9][10][11][12], secondly, the sensitizer is activated by irradiation with visible light of the appropriate energy [13][14][15]. Since the light penetration depth in tissue increases with the wavelength, an absorption maximum at the highest possible wavelength (red / near infrared) is taken for activation of the sensitizer [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Significant delay in tumor regrowth was achieved following meta-tetrahydroxyphenylchlorin-mediated intraperitoneal PDT and a toxicity study has determined the maximum tolerable light dose of ALA-mediated intraperitoneal PDT. (7,8) Hornung et al (9,10) showed that intraperitoneal PDT, as a minimally invasive procedure, could selectively debulk unresectable pelvic ovarian cancer in immunocompetent rats using the pegylated photosensitizer PEG-m-THPC, which was confirmed to be highly targeted to ovarian cancer in a rat model. Several clinical trials using first-generation photosensitizer dihematoporphyrin ether and porfimer sodium showed the therapeutic effects of PDT in treating peritoneal malignancy including ovarian cancer.…”
mentioning
confidence: 99%
“…Hornung et al have also studied the pegylated derivative of Foscan and proposed it as an efficient photodynamic agent [17,49]. The addition of four long PEG2000 side chains linked to mTHPC through a triazine group produced a tetrakis-(mmethoxypolyethylene glycol) derivative of 7,8-dihydro-5,10,15,20-tetrakis(3-hydroxyphenyl)-21-23-[H]-porphyrin (PEG-mTHPC).…”
Section: Covalent Attachment Of Polymermentioning
confidence: 99%